Signifikasi Leadership: Perspektif Sunni dan Syi’ah - Bahrul Ulum (Fakultas Syariah - IAI Al-Qolam Malang, 2018)
Disharmony on Sunni and Syi’ah groups are still being discussed among academics. The Sunni group reflects itself as a school that follows the teachings of the prophet who are forwarded by his companions. While Syi’ah reflects themselves as a follower of the prophet Muhammad through the path of ahlul bayt descendants of the prophet through Ali bin Abi Thalib and forwarded his offspring. Outside the study between Sunni and Syi’ah from the point of aqidah and the ordinances of worship, this paper intends to compare the theories of both groups by focusing on the concept of leadership, succession or the appointment of leaders, criteria of leaders, ordinances of appointment and who are eligible to appoint leaders. The authors draw the conclusion that the concept of Sunni politics in choosing leaders include; obedience to the leader, the power of the state head is sacred, the caliph is the shadow of God in the world, the leader is derived from the tribe of Quraisy, syuro is the urgent part, the appointment of the leader by ahlul halli wa al-aqdi. Unlike Sunni, Syi’ah groups use the concept of imamate or leadership that prioritized Ali and his descendants who are entitled to lead Muslim.